Analisis Strategi Pengembangan Agribisnis Kebun Strawberi di Desa Serang Kabupaten Purbalingga - Tegar, Agung; Lestari, Sagita Agus; Adiartanti, Yola; Sholiha, Yuzi Maulia; Raharja, Mahardhika Cipta (Program Studi Agribisnis, 2022)
Serang Village, Karangreja Sub-district, Purbalingga Regency is one of the best-performing villages at the national level because in 2013 it was successfully selected as the winner of Pakarti Utama I at the National Level in the Best Implementing Competition for Yard Yard Utilization (Heart of PKK) Regency Category. Serang village farmers first planted strawberries in 2003. The first seeds to be planted came from the remaining strawberry plantations of PT. Zeta Agro. Until now, Serang Village has been developed as a strawberry tourism village. This study aims to analyze the strategy of developing strawberry garden agribusiness in Seran Village, Purbalingga Regency. The research design is qualitative, with case study research techniques. Data collection methods used are interviews, observation and documentation. Based on the results of internal factors and external factors from the strawberry plantation agribusiness development strategy in Serang Village, it can be divided into four strategies, namely Strengths-Opportunities (S-O), Weaknesses-Opportunities (W-O), Strengths-Threats (S-T) and Weaknesses-Threats (W-T).